Sleep duration correlates with performance in ultra-endurance triathlon - Kisiolek, J. N.; Smith, K. A.; Baur, D. A.; Willingham, B. D.; Morrissey, M. C.; Leyh, S. M.; Saracino, P. G.; Mah, C. D.; Ormsbee, M. J. (International Journal of Sports Physiology and Performance, 2022)
The relationship between sleep duration, sleep quality, and race completion time during each stage of a 3-day ultra-endurance triathlon (stage 1: 10-km swim, 146-km cycle; stage 2: 276-km cycle; and stage 3: 84.4-km run) was investigated. Seventeen triathletes partook in sleep analysis throughout the ultra-endurance multiday triathlon using an actigraphy wristband. The participants wore the band to record objective sleep outcomes for approximately 4 days (1-2 d prerace, 3 race days, and 1 d postrace), except while racing. The total sleep time (TST; prerace: 414.1 [95.3] min, prestage 1: 392.2 [138.3] min, prestage 2: 355.6 [62.5] min, and prestage 3: 299.7 [107.0] min) significantly decreased over time (P < .05). Significant Pearson moment-product correlations were found between TST and subsequent race-day performance for race stage 1 (r = -.577; P = .019) and stage 3 (r = -.546; P = .035), with further analysis revealing that TST explained 33% and 30% of the variation in performance for stages 1 and 3, respectively. During a 3-day ultra-endurance triathlon, the TST was reduced and had a significant negative correlation to exercise performance, indicating that sleep loss was associated with slower performances. Sleep onset latency, wake episodes, and sleep efficiency did not significantly change over the course of this investigation, which may stem from the close proximity of exercise to sleep.